2018
DOI: 10.1103/physrevfluids.3.013502
|View full text |Cite
|
Sign up to set email alerts
|

Formation of eyes in large-scale cyclonic vortices

Abstract: We present numerical simulations of steady, laminar, axisymmetric convection of a Boussinesq fluid in a shallow, rotating, cylindrical domain. The flow is driven by an imposed vertical heat flux and shaped by the background rotation of the domain. The geometry is inspired by that of tropical cyclones and the global flow pattern consists of a shallow, swirling vortex combined with a poloidal flow in the r − z plane which is predominantly inward near the bottom boundary and outward along the upper surface. Our n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 17 publications
2
10
0
Order By: Relevance
“…This is because oscillations are viscously damped. Increasing Ek further we found that no eye formed for Ek > 0.23, consistent with [19]. For Ek less that 0.1, we find that the critical Reynolds number for oscillations falls dramatically as viscous effects reduce.…”
Section: Oscillatory Flowssupporting
confidence: 85%
See 1 more Smart Citation
“…This is because oscillations are viscously damped. Increasing Ek further we found that no eye formed for Ek > 0.23, consistent with [19]. For Ek less that 0.1, we find that the critical Reynolds number for oscillations falls dramatically as viscous effects reduce.…”
Section: Oscillatory Flowssupporting
confidence: 85%
“…They found that the flow was largely dependent on Reynolds number (and hence the temperature difference between the top and bottom of the vortex), with only a slight dependence on Prandtl number. The dependencies on aspect ratio, Ekman number (rotation rate) and Prandtl number (thermal diffusivity) were explored further in a follow up paper [19]. A detailed discussion of the dynamics of the tropical cyclone boundary layer, including how it may be swept into the eyewall, is given by Smith and Montgomery [20].…”
Section: Introductionmentioning
confidence: 99%
“…Possible applications of this study include tropical cyclones in the atmosphere, which are characterised by an aspect ratio close to 10 (approximately 10 km in height and a few 100 km in radius) as well as a moderate turbulent Ekman number, owing to the fact they develop close to the equator (see also Oruba et al 2018).…”
Section: A9-40mentioning
confidence: 99%
“…2007; Fischer, Rogers & Reasor 2020), a feature that is often observed prior to rapid intensifications. In actual tropical cyclones one can estimate the Ekman number in the range (Oruba, Davidson & Dormy 2018), which is small enough to motivate the asymptotic study presented here. It should be stressed, however, that in actual tropical cyclones, nonlinear effects cannot be a priori neglected and will thus modify the wave dynamics.…”
Section: Discussionmentioning
confidence: 99%